Treatment of multilevel degenerative lumbar spinal stenosis with spondylolisthesis using a combination of microendoscopic discectomy and minimally invasive transforaminal lumbar interbody fusion - WU, HAN (D.A. Spandidos, 2013)
Degenerative lumbar spinal stenosis (DLSS) has become increasingly common and is characterized by multilevel disc herniation and lumbar spondylolisthesis, which are difficult to treat. The current study aimed to evaluate the short-term clinical outcomes and value of the combined use of microendoscopic discectomy (MED) and minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) for the treatment of multilevel DLSS with spondylolisthesis, and to compare the combination with traditional posterior lumbar interbody fusion (PLIF). A total of 26 patients with multilevel DLSS and spondylolisthesis underwent combined MED and MI-TLIF surgery using a single cage and pedicle rod-screw system. These cases were compared with 27 patients who underwent traditional PLIF surgery during the same period. Data concerning incision length, surgery time, blood loss, time of bed rest and Oswestry Disability Index (ODI) score prior to and following surgery were analyzed statistically. Statistical significance was reached in terms of incision length, blood loss and the time of bed rest following surgery (P<0.05), but there was no significant difference between the surgery time and ODI scores of the two groups. The combined use of MED and MI-TLIF has the advantages of reduced blood loss, less damage to the paraspinal soft tissue, shorter length of incision, shorter bed rest time, improved outcomes and shorter recovery times and has similar short-term clinical outcomes to traditional PLIF.